COMBINING ABILITY ANALYSIS FOR NUTRITIONAL QUALITY AND YIELD IN MAIZE (ZEA MAYS L.) - RUMANA KHAN,; R. B. DUBEY, (The Bioscan, 2015)
A set of eight diverse inbred lines (P1 to P8) were crossed in diallel design to access their combining ability for yield and nutritional quality traits. The analysis of variance for combining ability revealed significant mean sum of squares due to GCA and SCA for all the traits. The ratio of σ2SCA/σ2GCA was greater than one for all the traits, thereby indicating the preponderance of non-additive gene effects in the expression of these traits. Inbred lines P5, P6 and P8 for grain yield per plant, P4, P5, P7 and P8 for oil content, P3 and P4 for starch content and P3, P6, P7 and P8 for protein content were identified as most promising parents due to having good general combining ability. Hybrid P6 x P8 showed highest positive significant SCA effects along with positive significant economic heterosis (9.14 %) for grain yield per plant. Hybrid P1 x P6 exhibited highest positive significant SCA effects for oil content. The hybrid P2 x P5 showed highest significant SCA effects, economic heterosis (3.33 %) and maximum per se performance (66.61 %) for starch content. Hybrid P2 x P6 depicted highest positive significant SCA effects with good economic heterosis (6.37 %) for protein content. Hence these hybrids appear to be very promising combination for actual exploitation.